2006
DOI: 10.1186/1471-2202-7-73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brain polarization on reaction times and pinch force in chronic stroke

Abstract: Background: Previous studies showed that anodal transcranial DC stimulation (tDCS) applied to the primary motor cortex of the affected hemisphere (M1 affected hemisphere ) after subcortical stroke transiently improves performance of complex tasks that mimic activities of daily living (ADL). It is not known if relatively simpler motor tasks are similarly affected. Here we tested the effects of tDCS on pinch force (PF) and simple reaction time (RT) tasks in patients with chronic stroke in a double-blind cross-ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(88 citation statements)
references
References 52 publications
7
79
1
1
Order By: Relevance
“…It might be that tDCS does not further increase voluntary activation, suggesting a ceiling effect at corticospinal levels. It has been documented that when there is little or no potential for improvement in a motor function, tDCS does not further enhance that function, whereas when potential for improvement in function exists, tDCS has the capacity to enhance that function (Hummel et al 2006). This might explain why tDCS produced no change in the muscle function of the healthy young male participants in our study.…”
Section: Discussionmentioning
confidence: 98%
“…It might be that tDCS does not further increase voluntary activation, suggesting a ceiling effect at corticospinal levels. It has been documented that when there is little or no potential for improvement in a motor function, tDCS does not further enhance that function, whereas when potential for improvement in function exists, tDCS has the capacity to enhance that function (Hummel et al 2006). This might explain why tDCS produced no change in the muscle function of the healthy young male participants in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have found improvements in motor function in stroke patients as measured by clinical scales or the JTT (Fregni et al, 2005; Hummel et al, 2005; Lindenberg et al, 2010; Mahmoudi et al, 2011; Khedr et al, 2013; Lefebvre et al, 2013) and an increase in pinch or grip force and a decrease in reaction times (Hummel et al, 2006; Stagg et al, 2012; Lefebvre et al, 2013). The improvement in reaction time with the ipsilesional stimulation protocol was correlated with the change in movement related activity under the anodal electrode (M1) and in the ipsilesional premotor cortex (Stagg et al, 2012).…”
Section: Application Of the Three Principles Of Polarizationmentioning
confidence: 99%
“…Decrease in GABA concentration is probably helpful for motor-related activity in the ipsilesional cortex (Clarkson et al, 2010). An increase in spontaneous/evoked firing rates might also drive some of the effects such as increase in pinch force (Hummel et al, 2006) and the increase in movement-related activity (Stagg et al, 2012). The long-lasting effect of tDCS on motor function is likely due to the after-effect of tDCS and its ability to engrave new firing patterns in memory.…”
Section: Application Of the Three Principles Of Polarizationmentioning
confidence: 99%
“…However, they may produce similar effects that may include increased excitability or normalization of inhibition, which coincide with improvements in motor behavior. 13 Methods of priming the motor cortex that are most relevant to rehabilitation include: (1) stimulation-based priming; 14-22 (2) motor imagery and action observation; 23-28 (3) manipulation of sensory input; 29-31 (4) movement-based priming; 7, 32-36 and (5) pharmacology-based priming. 37 Studies examining priming for the primary motor cortex (M1) are increasing in number.…”
Section: Introductionmentioning
confidence: 99%